2019
DOI: 10.12659/msm.919812
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanofiber Hydrogel Loaded with Platelet-Rich Plasma Promotes Wound Healing Through Enhancing the Survival of Fibroblasts

Abstract: Background: Hydrogels are ideal biological carriers in vivo and have been widely used in the treatment of wound healing through loading with or without bioactive substances. Platelet-rich plasma (PRP) is purified from autologous plasma and has known curative efficacy for wound healing. The combined efficacy of shorten poly-N-acetyl glucosamine (sNAG) hydrogels and PRP in the treatment of wound healing has not been previously assessed. Material/Methods: The cytotoxic and proliferative effects of PRP on fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Full-thickness excision skin wound/mice Encourage angiogenesis, fibroblast propagation in vitro and scar-free wound healing in vivo [67] Curcuma zedoaria polysaccharide Full-thickness for diabetic/ mice Promotion of wound contraction, enhanced angiogenesis, collagen synthesis, and deposition in treated wounds [68] Chitosan and silk fibroin Skin full-thickness for diabetic/mice Enhanced angiogenesis, nerve repair, and collagen synthesis and deposition [69] Oxidized dextran, hyaluronic acid, and antimicrobial peptide…”
Section: Applications Of Prp-loaded Hydrogels In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-thickness excision skin wound/mice Encourage angiogenesis, fibroblast propagation in vitro and scar-free wound healing in vivo [67] Curcuma zedoaria polysaccharide Full-thickness for diabetic/ mice Promotion of wound contraction, enhanced angiogenesis, collagen synthesis, and deposition in treated wounds [68] Chitosan and silk fibroin Skin full-thickness for diabetic/mice Enhanced angiogenesis, nerve repair, and collagen synthesis and deposition [69] Oxidized dextran, hyaluronic acid, and antimicrobial peptide…”
Section: Applications Of Prp-loaded Hydrogels In Wound Healingmentioning
confidence: 99%
“…Therefore, the release of anti-inflammatory drugs and growth factors must be guaranteed for a certain time, and compared with aerogels, hydrogels with water in network structures are favorable to wound healing. Zhang et al [67] assessed the combined efficacy of shortened poly-N-acetyl glucosamine (sNAG) hydrogels and PRP in the treatment of wound healing. The results indicated that sNAG hydrogels loaded with PRP showed curative efficacy during wound healing in mice.…”
Section: Applications Of Prp-loaded Hydrogels In Chronic Wound Healingmentioning
confidence: 99%
“…Fibroblasts play a crucial role in the wound healing process, and using fibroblasts, we explored the cytotoxicity and cytocompatibility of hydrogels [23]. The MTT assay showed that with increasing coculture time, our prepared hydrogels were nontoxic to cells, and the drug-containing hydrogels showed a tendency to promote the viability of HSF cells.…”
Section: Cur-p407/p188 Tsh Improves Wound Repairmentioning
confidence: 99%